1934
DOI: 10.1001/archotol.1934.03600020059007
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic Studies of the Petrous Portion of the Temporal Bone

Abstract: have stimulated a widespread interest in the subject of suppuration of the petrous pyramid during the past few years. As far back as 1904 Mouret1 carried out systematic anatomic studies on the petrous pyramid. At that time he evidenced his understanding of infection of the petrous tip. He stated that "if the cellular arrangement favors an infection of the mastoid process in the presence of suppuration of the middle ear and facilitates the retention of pus in that part of the temporal bone, it is easy to unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
2

Year Published

1935
1935
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(27 citation statements)
references
References 0 publications
0
25
0
2
Order By: Relevance
“…Mayerson et al reported an incidence approximately 1%. 4 Aberrant ICA can rarely occur bilaterally. 5,6 Embryologically, the vascular anomaly is a maldevelopment of the aortic arch I-III 2,7 with a hypoplasia of the carotid canal in the temporal bone.…”
Section: Discussionmentioning
confidence: 99%
“…Mayerson et al reported an incidence approximately 1%. 4 Aberrant ICA can rarely occur bilaterally. 5,6 Embryologically, the vascular anomaly is a maldevelopment of the aortic arch I-III 2,7 with a hypoplasia of the carotid canal in the temporal bone.…”
Section: Discussionmentioning
confidence: 99%
“…AICA enters the tympanic cavity through an enlarged inferior tympanic canaliculus, courses through the tympanic cavity under the cochlear promontory anteriorly and then medially enters the horizontal carotid canal through a dehiscence in the carotid plate [4]. Rarely, the carotid plate may be dehiscent allowing the artery to herniate into tympanic cavity [5]. The majority of the cases in literature diagnosed only after surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The vascular supply to the maxillary and mandibular regions comes from the external carotid artery. The course of ICA is different, normally the ICA ascends vertically, medial and anterior to the middle-ear cavity before bending sharply anterior and medially below the eustachian tube and cochlea, it then passes through the bony carotid canal in to the cranial cavity [10][11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%